2017
DOI: 10.1007/s00403-017-1752-1
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA effector RNA-induced silencing complex in hidradenitis suppurativa: a significant dysregulation within active inflammatory lesions

Abstract: Recently, we could show that the expression levels of the key regulators of the microRNA (miRNA) maturation and transport were dysregulated in inflamed hidradenitis suppurativa (HS) tissue (Heyam et al. in Wiley Interdiscip Rev RNA 6:271-289, 2015). The RNA-induced silencing complex (RISC) is the central element of the miRNA pathway and regulates miRNA formation and function. We investigated the expression of the RISC components, namely transactivation-responsive RNA-binding protein-1 (TRBP1), TRBP2, protein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 64 publications
0
12
0
1
Order By: Relevance
“…In the third study, Hessam et al (87) enrolled HS and psoriasis patients as well as healthy controls analyzed the expression profile of RNA-induced silencing complex (98) components (specifically, transactivation-responsive RNAbinding protein-1 (TRBP1), TRBP2, protein activator (PACT) of the interferon-induced protein kinase R, Argonaute RISC Catalytic Component-1 (AGO1) and Component- 2 (AGO2), metadherin, and staphylococcal nuclease and Tudor domain-containing-1 (SND1)), also in this case using RT QPCR, in their inflamed tissues (skin biopsies). The authors concluded, after RISC component comparison between skin biopsies of HS and psoriasis patients and healthy controls, that all RISC components were differentially expressed thus highlighting a possible role in the modulation of skin inflammation in HS patients.…”
Section: Transcriptomics: Differential Gene Expression In Hsmentioning
confidence: 94%
See 1 more Smart Citation
“…In the third study, Hessam et al (87) enrolled HS and psoriasis patients as well as healthy controls analyzed the expression profile of RNA-induced silencing complex (98) components (specifically, transactivation-responsive RNAbinding protein-1 (TRBP1), TRBP2, protein activator (PACT) of the interferon-induced protein kinase R, Argonaute RISC Catalytic Component-1 (AGO1) and Component- 2 (AGO2), metadherin, and staphylococcal nuclease and Tudor domain-containing-1 (SND1)), also in this case using RT QPCR, in their inflamed tissues (skin biopsies). The authors concluded, after RISC component comparison between skin biopsies of HS and psoriasis patients and healthy controls, that all RISC components were differentially expressed thus highlighting a possible role in the modulation of skin inflammation in HS patients.…”
Section: Transcriptomics: Differential Gene Expression In Hsmentioning
confidence: 94%
“…Another important aspect of gene expression regulation has been widely considered by Hessam et al (8587); in three independent studies, the authors analyzed miRNA expression profiles in inflammatory lesions from HS patients.…”
Section: Transcriptomics: Differential Gene Expression In Hsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small molecules that negatively regulate gene expression and serve as effective biomarkers due to their abundance, cell‐type and disease‐stage specificity, and stability in clinical samples. Prior studies showed that miRNA processing factors (including Drosha and Dicer), as well as components of the RISC complex (AGO proteins), are distinctly and progressively downregulated from normal, perilesional, to lesional HS skin. The presence of many inflammatory miRNAs in lesional HS suggests a typical inflammatory response obscuring keratinocyte contribution .…”
Section: Scientific Session 3: Pathophysiology Of Hidradenitis Suppurmentioning
confidence: 99%
“…Previous studies have shown that various inflammation-associated microRNAs (miRNAs) such as Drosha and Dicer are dysregulated in HS. [12][13][14] Dr Thomas Meyer showed that the downregulation of Drosha and Dicer observed in HS appears to be independent of promotor methylation/epigenetic modifications. Finally, Dr Katherine Hallock discussed the high rates of emergency department use in pediatric patients with HS.…”
Section: Session 1: Gaps In Hsdlooking Forward and ''Top Stories'' Momentioning
confidence: 99%